An Inquisitive Scrutiny of the Second Pillar and its Impacts Envisaged on the Ever-Changing CAP - WOLLEY, Benjamin Scott; TURK, Jernej (Agricultura Scientia, 2020)
This article provides an overview of the European Union’s Common Agricultural Policy (CAP), focusing on its Second Pillar. It begins with a meticulous analysis of the ongoing alterations of the Second Pillar. It further considers how these changes will impact upon CAP as a whole and while moving forward. At the same time the article thoroughly examines the Second Pillar’s implications on balanced rural development in European rural communities. With respect to rural communities, consideration is given to the diversity throughout the EU. The article also succinctly addresses both territorial rural development aspects and sustainable environmental management issues. Ultimately, several mainstream projections of further CAP reforms are discussed while noting some weakness that are inherent within true common policy.